ELECTRONIC STIMULATORS. LOW-FREQUENCY PHYSIOTHERAPEUTIC ELECTRONIC DEVICES - Elmurotova Dilnoza Baxtiyovna,; Makhramova Dinora Akhrorovna, (TADQIQOTLAR, 2025)
Low-frequency  physiotherapeutic  electronic  stimulators  are  vital  non-pharmacological interventions for musculoskeletal and neurological conditions. This article reviews their electrophysiological principles, technical classifications, clinical applications,  and  safety  considerations  at  a  graduate level. It details  how  electrical parameters modulate biological responses, distinguishing modalities like TENS, EMS, NMES, and IFT. The synthesis also covers regulatory oversight, efficacy evidence, and future directions, emphasizing the balance between technology, precise application, and patient safety for optimal rehabilitation outcomes.